The Dissociation between Polarity, Semantic Orientation, and Emotional Tone as an Early Indicator of Cognitive Impairment - Arias Tapia, Susana A.; Martínez-Tomás, Rafael; Gómez, Héctor F.; Hernández del Salto, Víctor; Sánchez Guerrero, Javier; Mocha-Bonilla, J. A.; Barbosa Corbacho, José; Khan, Azizudin; Chicaiza Redin, Veronica (Frontiers in Computational Neuroscience, 2016)
This study aims to identify early cognitive impairment by enabling the fast use of therapies; both can achieve improvements in life´s quality and prevent the progress of the disease. This research proposes a methodology based on the hypothesis that there is dissociation between semantic expression in orality and text, and between the associated physical expressions, facial gestures or emotions transmitted in a person’s tone of voice, dissociation that could be a possible indicator of cognitive impairment. Experiments were carried out with phrases, analyzing the semantics of the message and the tone of voice of patients through unstructured interviews to healthy people and patients with early Alzheimer's stage. The results showed this dissociation in cognitive impairment was effective, which arises from forming patterns of inconsistency between the analyzed elements. Although the results of this study are revealing, we believe that further testing is necessary to legitimatize the dissociation, treating it as a probable indicator. The conclusions and further works will allow us to continue this line of research in the future.